Academic Achievement in Children with Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
Academic achievement, measured by school-administered group tests, child attitudes and self-concept, and teachers rated school adaptive functioning were compared in 117 children with epilepsy and 108 with asthma, ages 8 to 12 years, and data were analyzed at the Indiana University Schools of Nursing, Education, and Medicine, Indianapolis.